Teacher Professional Education Curriculum Reconstruction (PPG) (An Overview of the Integration Between Nasr's Perennialism with Tri Education Center KH. Dewantara) - Smith, George; Arent, Ease; Thesalonika, Emelda (KnE Social Sciences, 2023)
Along with the shift from the manual era to the digital era, it has an impact on the quality of learning, especially increasing teacher qualifications. Future teachers need more expertise than traditional learning. They not only have pedagogical abilities but also spiritual and moral characters. The government seeks to produce future teacher candidates through teacher professional training (PPG). From the observations related to the PPG curriculum, it shows unpreparedness. This can be seen through the PPG curriculum which is still the same as S-1 education. In fact, according to the KKNI, the profession has a higher level than S-1, so PPG must have a distinctive feature that distinguishes it from graduates of S-1 education. PPG should not only circumvent the pedagogical section as a characterization of PPG. Therefore, there are at least 6 things that need to be considered regarding the formation of future teacher candidates through the PPG program, namely, 1) the history of teacher formation in Indonesia, 2) the challenges of the times, 4) how to teach students, 5) reformulating the PPG curriculum according to needs. future, and 6) the urgency of the PPG Curriculum. Keywords: Pendidikan profesi guru, curriculum, future